Pengabdian Masyarakat melalui Penerapan Metode Peer Counselor dengan Pendekatan Spiritual pada Pemrakarsa Kelompok Anti Kekerasan Seksual pada Anak - Nopi Nur Khasanah; Herry Susanto; Samsudin Samsudin (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Indonesian child protection commission or Komisi Perlindungan Anak Indonesia (KPAI) data bank showed the case of children as perpetrators as well as victims of sexual violence were very high in comparison to perpetrators or victims of physical and psychic violence. Intervention in schools is necessary to educate the children to behave according to the norms in society. This is the objective of the program and was realized by forming a peer counselor, optimizing the School Health Unit (SHU) services, educating children and parents about the early sex education, and conducting a spiritual approach by formation of psychosocial characteristics. The program was undertaken for approximately 2 months with the methods of training, community education, and advocacy. The program resulted in increased knowledge of early sex education in children (85%) and the parents (75%), increase of student PHBS (pretest: 76,9%; posttest: 92%), and decrease of children delinquency (pretest: 45%; Posttest: 30%).